Conversion from Heterometallic to Homometallic Metal–Organic Frameworks. Issue 51 (25th August 2020) - Song, Jeong Hwa; Lee, Giseong; Yoon, Jung Heum; Jang, Junyeon; Choi, Doosan; Yun, Heejun; Kwon, Kangin; Kim, Hojin; Hong, Chang Seop; Kim, Youngki; Han, Hogyu; Lim, Kwang Soo; et al.
Abstract: Two new heterometallic metal–organic frameworks (MOFs), LnZnTPO 1 and 2, and two homometallic MOFs, LnTPO 3 and 4 (Ln=Eu for 1 and 3, and Tb for 2 and 4 ; H3 TPO=tris(4‐carboxyphenyl)phosphine oxide) were synthesized, and their structures and properties were analyzed. They were prepared by solvothermal reaction of the C 3 ‐symmetric ligand H3 TPO with the corresponding metal ion(s) (a mixture of Ln 3+ and Zn 2+ for 1 and 2, and Ln 3+ alone for 3 and 4 ). Single‐crystal XRD (SXRD) analysis revealed that 1 and 3 are isostructural to 2 and 4, respectively. TGA showed that the framework is thermally stable up to about 400 °C for 1 and 2, and about 450 °C for 3 and 4 . PXRD analysis showed their pore‐structure distortions without noticeable framework–structure changes during drying processes. The shapes of gas sorption isotherms for 1 and 3 are almost identical to those for 2 and 4, respectively. Solvothermal immersion of 1 and 2 in Tb 3+ and Eu 3+ solutions resulted in the framework metal‐ion exchange affording 4 and 3, respectively, as confirmed by photoluminescence (PL), PXRD, IR, inductively coupled plasma atomic emission spectroscopy (ICP‐AES), and energy‐dispersive X‐ray (EDX) analyses. Abstract : Two new heterometallic metal–organic frameworks (MOFs), LnZnTPO, and two homometallic MOFs, LnTPO (Ln=Eu or Tb; H3 TPO=tris(4‐carboxyphenyl)phosphine oxide) were synthesized, and their structures and properties were analyzed. Solvothermal immersion of LnZnTPO in Ln 3+ solution resulted in the framework metal–ion exchange affording LnTPO (see figure).